Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/jhh.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory pulse pressure as a novel predictor for long-term prognosis in essential hypertensive patients

Abstract: The prognostic value of ambulatory blood pressure (BP) monitoring for long-term prognosis varies in recent studies. The study aimed to investigate the role of ambulatory BP parameters in mortality and cardiovascular (CV) events in hypertensive patients. A series of 412 participants (59.3±4.0 years) who received ambulatory BP monitoring for their fluctuated BP, either untreated or treated since 1995, were enroled. The mortality and CV events were obtained by follow-up and linked to the National Death Registry i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…PP was reported to be an independent risk predictor of CHD, stroke, or CVD in patients with T2D [26]. In fact, PP may be a better predictor of CHD events in high-risk patients, as it was reported to be better than SBP in predicting CHD in patients with T2D [27] or hypertension [7]. In addition, a recent study reported that patients with isolated systolic hypertension and prior CVD events have increased risk for recurrent CVD events in the presence of DBP less than 70 mmHg, supporting wide PP as an important risk modifier for the adverse effect of low DBP [28].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…PP was reported to be an independent risk predictor of CHD, stroke, or CVD in patients with T2D [26]. In fact, PP may be a better predictor of CHD events in high-risk patients, as it was reported to be better than SBP in predicting CHD in patients with T2D [27] or hypertension [7]. In addition, a recent study reported that patients with isolated systolic hypertension and prior CVD events have increased risk for recurrent CVD events in the presence of DBP less than 70 mmHg, supporting wide PP as an important risk modifier for the adverse effect of low DBP [28].…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, wide PP was suggested to represent large artery stiffness, which may be the dominant factor in the rise of SBP from middle age onward [5,6]. In the last decade, dozens of studies reported that wide PP is an independent risk factor (and in some cases, superior to SBP) in predicting CVD mortality or incident CHD [7][8][9][10]. It was observed that DBP less than 70 mmHg with SBP at least 120 mmHg (and hence wide PP) is associated with CVD risk equivalent to approximately 20 mmHg of additional elevation in SBP [11].…”
Section: Introductionmentioning
confidence: 98%
“…This finding is consistent with prior studies that have included more detailed measures of BP and observed that measures of central or 24-hour ambulatory PP are more predictive of all-cause mortality than central or ambulatory SBP. 41,42 In subgroup analyses, SBP was a relatively equal contributor to mortality risk in younger individuals and among men; SBP appeared to be a stronger predictor of death among blacks. Because increased PP reflects arterial stiffening, a well-recognized hallmark of vascular aging, hypertension is more likely to manifest as elevated SBP than elevated PP in younger compared to older age; 30 this phenomenon could at least partly account for the more prominent relationship between SBP and mortality in men and blacks, in whom death from any cause is more likely to occur at a younger age when compared to their counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…The associations of genotype with distinct quantitative traits, including daytime and nighttime PP, were analyzed separately. The accuracy of these devices was validated in our previous study [17]. This study protocol was approved by the Human Investigation Committee of the Institute of Biomedical Sciences, Academia Sinica and each participating hospital: Taipei Veterans General Hospital, Taichung Veterans General Hospital, Kaohsiung Medical University Chung-Ho Memorial Hospital, National Cheng Kung University Hospital, Cheng-Hsin Rehabilitation Medical Center, and Min-Sheng General Hospital.…”
Section: Methodsmentioning
confidence: 99%